Linguistic and Methodological Study of Lexical Derivations in German Languages - Abdurakhmanov Sirojiddin Muminkulovich (Genius Journals, 2022)
This article is about the historical linguistic and methodological study of lexical derivations in German languages. In German languages word formation, morphemic structure and their teaching methods are discussed. The grammar, lexicology, and word formation of German languages have been studied from a historical perspective. Examples of word formation through lexical derivations are given.
Keywords: Derivation; affix; inflectional language; analytic language